Analysis of land use and spatial planning in the Upstream Citarum watershed of West Java based on remote sensing data - Mukhoriyah Mukhoriyah; Samsul Arifin; Dony Kushardono; Mohammad Ardha; Fajar Yulianto (Journal of Degraded and Mining Lands Management, 2023)
The Upstream Citarum watershed has a critical essential role in maintaining the quality and quantity of its water resources, which are a source of drinking water, agriculture, fisheries, irrigation, and electricity generation. The upstream watershed acts as a water catchment area that contributes as a place to accommodate the availability of water, especially during the dry season, and also as a protector of the entire area, both downstream and middle, so that the carrying capacity of the ecological balance can be protected. The increasing total population was inversely related to the condition of land use which is decreasing in quality, so to fulfill these needs, there was a land conversion that caused changes in land use. The Landsat-8 satellite imagery, SPOT 7, and spatial planning maps were used to analyze the suitability and incompatibility of land use with spatial pattern plans, evaluation, and directions for controlling the use of space. The result of the most extensive existing land use in the Upstream Citarum watershed in 2021 used for fields is 30% of the total area of 66,831.66 ha. Meanwhile, the spatial pattern plan was classified into protected and cultivated areas. The built-up area has the largest area, 35% or 75,223.96 ha. The results of the suitability of land use classes obtained that the level of suitability between the existing land use and the spatial pattern plan from the Maps of Regional Spatial Planning with the appropriate class was 52.50% or 96,205.43 ha, and the unsuitable class was 47.50% or 87,028.75 ha.